Little Dog Moon - Trottier, Maxine; Fernandez, Laura; Jacobson, Rick. (Toronto : Stoddart Kids, 2000)
"A brave dog leads a young girl and boy on a breathtaking journey to freedom. Readers will be enthralled by this inspiring story about family, sacrifice and strength of spirit" Cf. Our choice, 2001.
1-3.
6 and up.
Accelerated Reader AR
Keywords: Dogs -- Fiction; Monks -- Fiction -- China; Sacrifice -- Fiction; Escapes -- Fiction; Picture books for children; Chiens -- Romans, nouvelles, etc. pour la jeunesse; Moines -- Romans, nouvelles, etc. pour la jeunesse -- Chine; Sacrifice -- Romans, nouvelles, etc. pour la jeunesse; Évasions -- Romans, nouvelles, etc. pour la jeunesse; Livres d'images pour enfants; Tibet (China) -- Fiction; Tibet (Chine) -- Romans, nouvelles, etc. pour la jeunesse